PERBANDINGAN PEMBAYARAN PAJAK SEBELUM DANSAAT KEPEMIMPINAN PRESIDEN JOKOWI PERIODE 1: (Studi Empiris pada Perusahaan Industri Barang Konsumsiyang Terdaftar di BEI periode 2012–2017) - Kustandi, Evina (Media Akuntansi dan Perpajakan Indonesia, 2020)
This research was implemented to determine if there were any differences in tax payment activities before and during the first-period leadership of President Jokowi. This research used manufacturing companies in the consumer goods industry sector listed on the (Indonesia Stock Exchange) IDX which were counted with effective tax rate model as research sample. The researcher observed the company data starting from 2012 until 2017. In order to obtain the data, the researcher used a purposive sampling method. However, the researcher obtained only 72 company data. The result of the parametric Paired Sample t-Test stated that there were no significant differences regarding the corporates tax payment activities (Sig value = 0.20) between the leadership before and during President Jokowi’s first presidential period which were calculated with the effective tax rate model. It was seen from the test result that the tax payment form companies did not make a any significant difference before and during President Jokowi’s predential period.